OTOMATISASI POLIGON DARI AWAN TITIK UNTUK BASIS PEMODELAN 3D MULTI-CITRA MONOSKOPIK - Kamal, Lahij
The development of technology nowadays demands that all processes can be carried out quickly and efficiently. This is very important considering the need for 3D models of buildings is increasing so there is a need for new methods of processing. In this research, 3D modeling is done through the use of data from the Close Range Photogrammetry Multi-Image which then produces a dense point clouds through the SfM (Structure from Motion) and MVS (Multiview Stereo) methods. In the use of technology, both Geographic Information Systems (GIS) and Building Information Modeling (BIM), 3D models are needed in the form of building geometry so that it is necessary to process point clouds into building polygon geometries through manual digitizing. The manual digitizing process is carried out through a monoscopic multi-image measurement system with the principle of space intersection. To reduce processing time and workload in the manual digitizing, automation of 3D polygon geometry from point cloud data through Polyfit is used for the basis of further digitizing purposes. Building polygons that have been formed through automation will be transformed (due to changes in coordinate values by the software) and continued with the depiction of building facade details through manual digitizing on the Photomodeler software. The results of this study are 3D model of building that is formed automatically with additional building details through manual digitizing.